INTERNET OF THINGS (IoT) PADA SISTEM MONITORING HUMIDITY AND TEMPERATURE AIRCRAFT BATTERY STORAGE INTERNET OF THINGS (IoT) IN HUMIDITY AND TEMPERATURE MONITORING SYSTEM AIRCRAFT BATTERY STORAGE - Sujatmiko, Alfhiyan; Sadi, Sumardi; Mulyati, Sri (Universitas Muhammadiyah Tangerang, 2024)
AbstractAircraft battery is a backup source of electricity on aircraft, for maintaining the performance of an aircraft battery, there are rules that must be implemented, one of which is the storage process on the aircraft battery. In the process of storage, aircraft battery has its own shelf life for the stored voltage, this depends on the humidity and temperature of the storage room. To monitor and control the data from time to time, the nominal value of the humidity and temperature of the storage room, an automatic monitoring device is made. This tool consists of WEMOS D1 R2, ARDUINO UNO, LED, LCD, BUZZER, smartphone, and 4 DHT22 sensors as 4 zones of reading area from the sensor and will then be connected to the Blynk application. The DHT22 sensor will send input humidity and temperature data to WEMOS D1 R2 and ARDUINO UNO, from ARDUINO UNO the data will be processed and processed for the LCD reading system and for the warning system for the user, from WEMOS D1 R2 then the data will be processed and sent and displayed to the Blynk application over the internet. From these tools, the largest error value is 0.4, and the largest standard deviation is 0.085, so that the data error rate or tolerance is 0.5494%.Keywords: humidity and temperature, WEMOS D1 R2, DHT22, Blynk